Impact of socio-economic and input variables on the profitability of dairying: A study in women coopearative society - Suresh, R; Rao, K Sarjan; Reddy, Y Ravindra; Sharma, G R K; Punyakumari, B (Indian Journal of Animal Production and Management, 2018)
Dairying is considered as the ever income supporting enterprise in India. High input cost results in less profitsor losses in dairying. The present study was conducted at one of the successful women dairy cooperative inTelangana State to know the impact of socio economic and input variables on the profitability from dairying.The independent variables such as educational status, herd size, family members and landholding werepositively and significantly correlated with milk production. The inputs were positively and significantlycorrelated with total milk production and income from milk in both member and non members groups. Thecoefficients of cost of dry fodder, concentrate and labour cost showed a positive and significant (P